Stress materno in gravidanza, disturbi mentali materni e neurosviluppo fetale: una narrative review - Autori vari, (Il sogno della farfalla, 2024)
Maternal-fetal relationship during pregnancy has been object of an extensive number of research studies with the aim to investigate the connection between maternal stress and physiological fetal neurodevelopment. In the Human Birth Theory, the psychiatrist Massimo Fagioli postulates that the fetus is exclusively a biological phenomenon, affirming that birth marks the beginning of both physical and mental life. In this theoretical framework, the aim of this paper is to propose an indepth analysis of current scientific literature on this topic, with a specific focus on those articles examining the role of maternal mental illness and cortisol, one of the major stress hormones, in the antepartum phase of pregnancy. The aim of the authors is to open a debate between the neurobiological and psychiatric fields with the objective to bring into question the idea that neuro-fetal development is influenced by maternal mental state.